The Role of Workplace Well-being in Organizational Adaptation to Global Changes based on the Results of Research Conducted among Hungarian Enterprises - Dr. Juhasz, Gabor; Dr. Jarjabka, Ákos; Dr. Sipos, Norbert (Anali Ekonomskog fakulteta u Subotici, 2025)
Our study aims to draw attention to the role and significance of the factors influencing workplace well-being and the relationships between them in the process of developing an organizational HR strategy. In our study, we will deal with the concept of workplace well-being, work-life balance, job satisfaction, and the effects of the relationships between dimensions on organizational operational efficiency. Our research aims to draw attention to the prominent role that workplace well-being plays in adapting to external environmental changes and retaining the workforce. In the questionnaire survey conducted among enterprises operating in Hungary, we processed data from 205 respondents using computer mathematical-statistical methods. The research results confirmed our hypothesis that workplace well-being and its determining factors are closely interconnected and have a significant impact on work motivation and job satisfaction. Based on the results, it is recommended to introduce interventions that increase work motivation and employee satisfaction, and to integrate well-being measures more closely into HR strategy. The results of the article highlight that the complex interrelation of influencing factors of workplace well-being, job satisfaction, and work-life balance should not be treated separately, as it is clear from exploratory results that intervention in one factor has a direct impact on the others. Consequently, non-systematic treatment may lead to a counterproductive HR strategy. The results of our research, which cannot be considered representative, were influenced by the relatively low number of samples, which we are constantly expanding since our present study reports the first partial results of our research project.